Touching behavior of rural and urban people in Iloilo. - Valera, Maria Florita Lagtapon
This is a study on touching behavior of rural and urban people in Iloilo. The study may appear comparative but in fact is not. The researcher aims to determine the particular parts of the body touched by the males and females of the rural area and the males and females of the urban area. It also aims to determine the occasion of touching behavior of the Ilonggo males and females in the rural area as well as the males and females of the urban area. The first hypotheses is, there is no significant difference between gender in the touching behavior of Ilonggo in rural area and there is no significant difference between gender in the touching behavior of Ilonggo in the urban area. The second hypotheses is, there is no significant difference in the occasion of touching behavior of gender and significant others in rural and there is no significant difference in the occasion of touching behavior of gender and significant others in the urban area. The researcher used accidental sampling in the pre-test conducted in the UPV High School and St. Paul's Academy in Iloilo. Final respondents in Marillac Academy and De Paul College were chosen with the use of "fishbowl" technique by Fox. The Spearman Rank Order Correlation and Chi-Square test of Independence were used to test the hypotheses. Finally, the researcher discovered that there is a significant difference in touching the buhok (hair) and butkon (arm), and kamot (hands) of their father , mother and opposite-sex friend by the rural Ilonggo as well as the occasion they touched it. The guya (cheek) has a significant difference in the occasion of touching behavior by the males and females of urban area. The guya (cheek) and butkon (arm) are the versatile areas in the urban while buhok (hair) for the rural.